Playing the viola : conversations with William Primrose - Dalton, David (David J.); Primrose, William, 1904-1982.; Oxford University Press (Oxford [England] ; New York : Oxford University Press, 1988)
Before the death of the renowned violist William Primrose in 1982, David Dalton engaged the musician in a lively series of conversations which touched on almost all aspects of viola technique, performance, repertoire, recording, and history. This book is a transcription of this dialogue, containing illuminating advice on holding the viola, bowing, tone, fingering, and practicing, all supported by copious illustrations and musical examples, as well as insights on repertoire for the viola--"an instrument without tradition"--And on performances of the great concertos by Bartok and Walton. Punctuated with frankness and humor, this book is a tribute to one of the greatest artists of this century.--Publisher description.
1. Viola via Violin? 2. Teacher and Student 3. The Lesson 4. On Practising 5. Holding the Viola 6. The Art of Bowing 7. More on Bowing and Tone 8. The Matter of Fingering 9. Left-hand Techniques 10. Other Left-hand Considerations 11. About Performing 12. On Stage 13. The Repertoire 14. Performance Practice and Interpretation 15. Programming 16. Recordings: How, and What to Make of Them 17. Competitions 18. Toward a Career Eulogy Index
Includes bibliographical references and index.
Keywords: Viola -- Instruction and study